Student Voices to Integrate Planetary Health Into Nursing Curriculum - Chircop, Andrea; Barber, Brittany; Doucet, Lisa; Zhou, Fenggang; Curry, Karen; Houk, Shauna; Fulford, Alexander; States, Chelsa (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2026)
Embedding planetary health into nursing curricula is a priority as climate change, biodiversity loss, and pollution are accelerating globally and across Canada (Government of Canada, 2024). Evidence-informed frameworks such as the Planetary Health Education Framework (Faerron Guzmán et al., 2025) and the National Nursing Education Framework (Canadian Association of Schools of Nursing, 2022) provide guidance. To adopt the best way forward, it is vital to also seek nursing students’ views on the positioning of planetary health within their nursing education as they are the future custodians of the planet and nursing leaders. Taking an appreciative inquiry approach, this study conducted focus groups with undergraduate students to seek their understanding of the positioning of planetary health within our current curriculum and ask their opinions on how to embed planetary health concepts and processes. The resulting recommendations, along with existing research and guiding frameworks, strengthen support and offer a clear road map on how to integrate planetary health into our nursing curriculum.